Craniofacial morphology of Patient with Operated Unilateral cleft Lip and Palate (A cephalometric study) (Mustansiria Dental Journal, 2018)
Background:Growth disorders associated with inborn defects, injuries or surgeries can restrict the development of the palatoalveolar complex and initiate the development of jaw and orthodontic anomaliesAim of the study: to assess the skeletal craniofacial morphology of patients with operated unilateral cleft lip and palateMaterials and Methods: lateral cephalometric radiographs were taken for 20 adult of Iraqi operated unilateral cleft lip and palate patients. Twelve angular measurements and seven linear measurements were compared with control group selected on the bases of satisfactory facial esthetic matching with age.Results: A significant differences were observed between cleft patients and non cleft individuals in that, cleft patients have smaller mean value mandibular angular measurements max-mand angle, N-S-GN angle with short body length while the maxilla demonstrates a retrusive position and results in the concave profile appeared by increase N-A-Pog angle at p